A novel strategy to capture phosphate as high-quality struvite from the sewage sludge ash: Process, mechanism and application. (1st November 2021) - Li, Shuaishuai; Zeng, Wei; Ren, Ziyan; Jia, Ziyue; Peng, Xiaojing; Peng, Yongzhen
Abstract: As a promising phosphorus source, phosphorus recovery from sewage sludge ash is necessary to ensure sustainable phosphorus cycle and management. To achieve these targets, a novel strategy including phosphorus capture by acid-resistant adsorbent from acid-extract of sewage sludge ash and repeated enrichment in eluent was first proposed in this study. Over 93% of phosphorus was extracted by H2 SO4 acidification at pH of 2.0, and a tailored acid-resistant adsorbent recovered almost all the extracted phosphorus in acid-extract of sewage sludge ash. The fitting results of multiple models showed that the rate-limiting step for phosphorus recovery was chemical reaction, and the maximum recovery capacity of acid-resistant adsorbent was 41.7–44.0 mg/g. Characterization results of X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy and Zeta potential suggested that the recovery mechanism of acid-resistant adsorbent for phosphorus included ligand exchange, inner-sphere complexation and electrostatic attraction. After 8 cycles of recovery-repeated enrichment, the phosphorus in eluent was enriched about 6.7 times. Over 99% of phosphorus in eluent was recovered as struvite by adding external magnesium and ammonium at pH of 8.5. The content of heavy metals in recovered struvite were far below the utilization standard of plant fertilizer, indicating that the phosphorus in sewage sludge ash could be recovered in the form of high-quality phosphorus fertilizer. Graphical abstract: Image 1 Highlights: A novel strategy for phosphorus capturing from sewage sludge ash was proposed. All phosphorus species became orthophosphate at incineration temperature above 650 °C. Over 93% phosphorus was extracted at pH 2.0 and recovered by the tailored adsorbent. Above 85% recovery capacity of tailored adsorbent was kept in 8 regeneration cycles. Phosphate enriched eluate could recover as struvite with negligible heavy metal risk.